Meiosis in haploid yeast - Wagstaff, Joseph E. (Proc Natl Acad Sci U S A, 1982)
Haploid yeast cells normally contain either the MATa or MATα mating-type allele and cannot undergo meiosis and spore formation. If both mating-type alleles are present as a consequence of chromosome III disomy (MATa/MATα), haploids initiate meiosis but do not successfully form spores, probably because the haploid chromosome complement is irregularly partitioned during meiotic nuclear division. We have demonstrated that the ochre-suppressible mutation spo13-1 enables haploid yeast cells disomic for chromosome III and heterozygous at the mating-type locus to complete meiosis and spore formation, yielding two haploid spores. Previous studies have shown that the absence of the wild-type SPO13 gene function permits diploid cells to bypass homologous chromosome segregation at meiosis I and proceed directly to meiosis II. During spo13-1 haploid meiosis, cells enter prophase of meiosis I. Genetic recombination, monitored on the chromosome III disome, occurs at levels similar to those seen in diploids, indicating that the level of exchange between homologs is an autonomous property of individual chromosomes and not dependent on exchange elsewhere in the genome. Exchange is then followed by a single meiosis II equational chromosome division. Recombination in spo13-1 haploids is blocked by the spo11-1 mutation, which also eliminates recombination between homologous chromosomes during conventional diploid meiosis. We conclude that Spo(+) haploids expressing both a and α mating-type information attempt a SPO13-dependent meiosis I division, and that this division, in the absence of paired homologous chromosomes, is responsible for the failure of such haploids to complete normal gametogenesis. Our observations support the conclusion that initiation and completion of meiosis II and spore formation are not dependent on either completion of meiosis I or the presence of a diploid chromosome complement. IMAGES: